The Role of International Committee of the Red Cross on the Russia-Ukraine War - Ahmad Faris Fauzan; Djayeng Tirto S; Achmed Sukendro; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
This article aims to analyze and describe how many victims there are in the current Russia-Ukraine war. Basically humanity is the basis of life anywhere. So the importance of presence of the International Committee of the Red Cross (ICRC) as part of humanitarian law to deal with existing casualties. We can see how the war that occurred could not be finished simply. So besides focusing on the war, first aid is also needed for victims of the war. This article uses a qualitative approach with a literature review design related to the role of ICRC in this war. The data was collected by compiling sources from various kinds of literature such as reading books, websites and discussions with experts and competent groups. The results show that there were many casualties from both the Russian and Ukrainian sides in the war that took place. The ICRC as an important body in humanitarian law is needed to be able to carry out its duties properly.